Launch and post-launch prices of injectable cancer drugs in the US: clinical benefit, innovation, epidemiology, and competition - Michaeli, Daniel; Michaeli, Christoph T. (PharmacoEconomics, 2024)
Background: Rising cancer drug prices adversely affect patients’ adherence and survival. Objective: We aimed to identify and quantify factors associated with launch prices and post-launch price changes of injectable cancer drugs in the US from 2005 to 2023. Data and Methods: All anticancer drugs with US FDA approval between 2000 and 2022 were identified in the DrugsFDA database. The sample was then restricted to cancer drugs covered under Medicare Part B (injectable drugs). Data characterizing each drug’s clinical benefits, disease epidemiology, approved indications, competition, and price were obtained from FDA labels, the Global Burden of Disease study, and the Centers for Medicare and Medicaid Services. The association between launch/post-launch prices and collected variables was assessed in random-effects regressions.Results: Of 170 cancer drugs with FDA approval between 2000 and 2022, we identified 66 (39%) injectable cancer drugs with quarterly price data from 2005 to 2023. In 2023, mean prices amounted to $27,688 per month, with an average price increase of 94% from 2005 to 2023. Launch and post-launch price changes were significantly associated with the treated disease epidemiology. A 1% decline in disease incidence was associated with a 0.2511% (p = 0.008) increase in launch prices and a 0.0086% (p = 0.032) annual increase in post-launch prices. Accordingly, launch prices were 120% (p = 0.051) higher for orphan than non-orphan drugs, with 3% (p = 0.008) greater annual post-launch price increases. Post-launch prices declined by up to −2% annually as new supplemental indications were approved for the same drug. We found no consistent association between launch/post-launch prices and the drugs’ clinical benefit in terms of overall survival, progression-free survival, and tumor response. The market entry of new competitors was not associated with price reductions. 28 of 33 drug pairs within the same class had positive correlation coefficients. Pearson correlation coefficients were high (>0.80) for PD-1/PD-L1 inhibitors, CD38 antibodies, CD20 antibodies, HER2 antibodies, and mTOR inhibitors. Conclusions: Cancer drug prices regularly increase faster than inflation; however, there is no evidence that launch prices and post-launch price changes are aligned with the clinical benefit a drug offers to patients. In particular, patients with rare diseases experience greater price increases for their orphan drugs. There is no evidence that brand-brand competition results in drug price reductions.
Online veröffentlicht: 19. Oktober 2023
Gesehen am 04.01.2024